2004
DOI: 10.1097/01.ccm.0000104114.72614.bc
|View full text |Cite
|
Sign up to set email alerts
|

Effect of neuromuscular blocking agents on gas exchange in patients presenting with acute respiratory distress syndrome*

Abstract: Use of NMBA during a 48-hr period in patients with acute respiratory distress syndrome is associated with a sustained improvement in oxygenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
249
3
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 288 publications
(265 citation statements)
references
References 46 publications
5
249
3
8
Order By: Relevance
“…Also, it was not powered adequately for mortality, though the authors did report a non-significant trend toward decreased ICU stay and decreased 28-day mortality (favouring cisatracurium). 10 In a follow-up study, Forel et al used a similar study design and found that early use of cisatracurium infusion in ARDS also decreased serum and pulmonary concentrations of pro-inflammatory markers when compared with control. 11 The current work by Papazian et al has built on these studies.…”
Section: Commentarymentioning
confidence: 99%
“…Also, it was not powered adequately for mortality, though the authors did report a non-significant trend toward decreased ICU stay and decreased 28-day mortality (favouring cisatracurium). 10 In a follow-up study, Forel et al used a similar study design and found that early use of cisatracurium infusion in ARDS also decreased serum and pulmonary concentrations of pro-inflammatory markers when compared with control. 11 The current work by Papazian et al has built on these studies.…”
Section: Commentarymentioning
confidence: 99%
“…The NMBA group also had faster weaning of PEEP, indicating improved lung compliance at the end of the 5-d study period. 17 A separate randomized trial by Forel et al 21 reported similar improvements in oxygenation with the use of NMBAs in early ARDS. 21 The mechanism for improved oxygenation remains unclear.…”
Section: Pro: Nmbas May Improve Survival In Ardsmentioning
confidence: 95%
“…[22][23][24] The reduction in oxygen consumption might decrease demand for oxygen delivery and carbon dioxide removal, ultimately resulting in decreased cardiac output and decreased pulmonary blood flow, which then may minimize the edema seen at the alveolar-capillary level in ARDS. What is interesting to note is that for both the Gainnier et al 17 and Forel et al 21 trials, the improvement in oxygenation persisted throughout the 5-d study period, well beyond the 48 h of muscle paralysis, 17,21 which suggests that the reduction in oxygen consumption cannot be the primary mechanism of improved oxygenation.…”
Section: Pro: Nmbas May Improve Survival In Ardsmentioning
confidence: 98%
See 2 more Smart Citations